Pengaruh Kompleksitas Pajak terhadap Kepatuhan Wajib Pajak: Apakah Kultur Nasional Memiliki Peran? - Viliona Viliona; Ari Budi Kristanto (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2021)
This study examines the effect of tax complexity on tac compliance, and examines the effect of national culture as moderating variables between the relationship of tax complexity and tax compliance. Moreover, the national culture itself consist of 6 dimensions, namely masculinity, individualism, uncertainty avoidance, power distance, short-term normative orientation, and indulgences. The population in this study are all countries around the world. The sample consist of countries that were included in the studies of Tax Effort 2015 and National Culture 2015. After sorting the data based on the variables, the sample were 45 countries. The analysis technique is using Moderated Regression Analysis (MRA). Before conducting the test, the data was tested using the classical assumption test. The result showed that tax complexity had no effect on tax compliance (beta -0,307; significance 0,426). This study also proves that national culture with the dimensions of masculinity, individualism, uncertainty avoidance, power distance and indulgence as moderating variables can strengthen the negative relationship between tax complexity and tax compliance. In addition, the dimension of short-term normative orientation cannot moderate the relationship between tax complexity and tax compliance. This research can be used as an evaluation material for the government in considering the role of national culture in solving problems related to non-compliance with taxpayers in a country. Keywords: Tax Complexity, Tax Compliance, and National Culture